Biochemical Studies of Matrix Metalloproteinase (MMP) and tissue inhibitor of Metalloproteinase (TIMP) as New Biomarkers in HCV - Chronic liver disease - Elgzar, M. Y; Elemshaty, M.H; Amar, E.A.T; Abdel Atty, A.M; Elgareb, A.H. H (Journal of medical and pharmaceutical sciences, 2017)
The present study aimed to investigate serum levels of Matrix Metalloproteinase (MMP9) and tissue inhibitor of Metalloproteinase (TIMP-1) as new biomarkers in HCV Chronic liver disease. Patients and methods: The study included 35 patients suffering from Chronic liver disease attending at Gastro Entrology Surgical Center (GEC), Mansoura University from 2016 to 2017 and 25 healthy individuals (HI) used as control group ,the studied groups were categorized into 14 patients (9 men and 5women; mean age 53.34±9.46yrs) suffering from HCC associated with HCV infection, 11patients (9 men and 2 women; mean age 52.34±9.14yrs) suffering from LC associated with HCV infection and 10 patients (7 men and 3women; mean age 48.9 ± 12.4yrs) suffering from Chronic Hepatitis (CH). Sera of all individuals were examined for TNF-α, LDH, AFP, ALT, AST, Albumin, T.Bilirubin, GGT, MMP-9 and TIMP-1 .  Results: The obtained results showed a significant increase in serum ALT, AST, total Bilirubin and GGT and significant decrease of Albumin in liver disease groups (I, II and III) compared with Group IV. Significant increase in serum MMP9, TIMP1 in groups (I, II and III) when compared with HI group (IV). Significant correlation was recorded between MMP9 and TIMP1 in one hand and between each one with AST, T. bilirubin and Albumin concentration. Serum concentrations of TNF-α, AFP were elevated significantly in HCC patients compared to LC and CH but the difference between LC and CH was elevated significantly only (p
Keywords: Hepatitis C virus; Liver fibrosis; Matrix metalloproteinase-9; tissue inhibitor of Metalloproteinase Biopsy; Fibro scan